By which tools?: A critical comparative analysis of pedagogic discourse for the creative arts in formal and informal classrooms in a working class post-apartheid context - Mokou, Goitsione (School of Education, 2017)
This research study was motivated by a research project which observed differences in achievement levels within the creative arts classroom between working class schools and middle class schools. These achievement gaps were largely attributed to inadequate pedagogue skills and content knowledge and the lack of adequate materials in working class schools. The research project sought a way to address this problem by initiating a 2-year pilot extracurricular project at one working class school by introducing a methodology, freespace, which sought to simultaneously bring in facilitators and practitioners who work in the creative arts and also to provide the resources needed. Freespace is described as an informal educational tool which draws its principles from popular education discourse. The purpose of this research study was to conduct a comparative analysis of the transmission of pedagogic discourse between the informal classroom (freespace) and the formal classroom; with a particular emphasis on the regulative discourse inherent to both practices. Furthermore, this research study sought to understand the sort of contribution that informal pedagogic practice might make to the formal creative arts classroom. In order to conduct this study I employed Bernstein's model of the pedagogic device to set out my research design. I also used his methodology of developing an external language of description for coding my data. I conducted interviews with pedagogues and classroom observation to collect my data. The interview data were coded using Maton's development of Bernstein's code theory, namely Legitimation Code Theory (Specialisation) using epistemic and social relations, to allow me to capture the values and intentions of the pedagogues (the intended curriculum). To capture the enacted curriculum, I used Bernstein's framing dimensions to code the data from the classroom observations. The findings of this research study suggest that the pedagogic discourse(s) of both the formal and informal context and their inherent regulative discourses privilege an ideal learner-knower. In conclusion, this research study seeks to suggest that while the cultivated gaze has proven beneficial with respect to inculcating learners into a given dominant discourse, particularly within the creative arts; that an argument can also be made for adopting a social gaze in this particular context (working class school) in order to a) allow learners to be adequately socialised into art practise and b) allow for a plurality of the epistemic in order that both the dominant gaze and notions of achievement and effective pedagogy might be disrupted.